Assessment of Cellular Responses after Short- and Long-Term Exposure to Silver Nanoparticles in Human Neuroblastoma (SH-SY5Y) and Astrocytoma (D384) Cells - Teresa Coccini; Luigi Manzo; Vittorio Bellotti; Uliana De Simone (The Scientific World Journal)
Silver nanoparticle (AgNP, 20 nm) neurotoxicity was evaluated by an integrated in vitro testing protocol employing human cerebral (SH-SY5Y and D384) cell lines. Cellular response after short-term (4–48 h, 1–100 μg/ml) and prolonged exposure (up to 10 days, 0.5–50 μg/ml) to AgNP was assessed by MTT, calcein-AM/PI, clonogenic tests. Pulmonary A549 cells were employed for data comparison along with silver nitrate as metal ionic form. Short-term data: (i) AgNP produced dose- and time-dependent mitochondrial metabolism changes and cell membrane damage (effects starting at 25 μg/ml after 4 h: EC50s were 40.7 ± 2.0 and 49.5 ± 2.1 μg/ml for SH-SY5Y and D384, respectively). A549 were less vulnerable; (ii) AgNP doses of ≤ 18 μg/ml were noncytotoxic; (iii) AgNO3 induced more pronounced effects compared to AgNP on cerebral cells. Long-term data: (i) low AgNP doses (≤1 μg/ml) compromised proliferative capacity of all cell types (cell sensibility: SHSY5Y > A549 > D384). Colony number decrease in SH-SY5Y and D384 was 50% and 25%, respectively, at 1 μg/ml, and lower dose (0.5 μg/ml) was significantly effective towards SH-SY5Y and pulmonary cells; (ii) cell proliferation activity was more affected by AgNO3 than AgNPs. In summary, AgNP-induced cytotoxic effects after short-term and prolonged exposure (even at low doses) were evidenced regardless of cell model types.